Identifying scale economies for different types of water supply organizations in Japan - Takuya Urakami (European Regional Science Association (ERSA), 2005)
Although water supply systems include activities such as water intake; water purification; and water distribution, many water supply organizations are not always equipped with all three activities. In fact, Japan has two types of water companies: one that operates water intake and water purification (type 1); and the other which mainly operates water distribution (type 2). Many previous studies have attempted to identify scale economies for water supply organizations, but have failed to take into account which water supply systems operate. In this analysis we categorize Japanese water supply organizations into three types: type 1 - which operates water intake and water purification; type 2a - which not only operates water distribution, but also operates water intake and water purification; and type 2b - which operates water distribution, but purchases water from type 1 companies. After that, we estimate scale economies for each type of water supply organization using translog cost function. Furthermore, we take into account their water sources, especially type 1 and type 2a, because we consider that differences of water sources might affect the cost structure of water supply systems.
Keywords: 330